BENTUK KERJASAMA MUDHARABAH ANTARA NELAYAN TANGKAP DAN PEMILIK KAPAL DALAM MENINGKATKAN KESEJAHTERAAN NELAYAN DI KELURAHAN TANJUNG BATU, KECAMATAN BANAWA, KABUPATEN DONGGALA - Lanonci, Lathifah (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to identify the form of mudharabah partnership between fishermen and boat owners and to analyze the profit-sharing mechanism applied. A descriptive qualitative approach was used, employing observation, interviews, and document analysis involving fishermen, boat owners, and community leaders. The mudharabah cooperation is based on trust and familial bonds, without written agreements, with a profit-sharing ratio of 40% for fishermen and 60% for boat owners. While the system modestly improves fishermen’s welfare, fishermen also bear losses when there is no catch, which deviates from the pure principles of mudharabah. Both parties perceive the profit-sharing as fair, though the absence of a written contract poses a risk of disputes. External factors such as weather and fluctuating fish prices hinder more significant welfare improvements. There is needs to strengthen transparency and legal protection in the mudharabah system. Policy recommendations include implementing Islamic insurance schemes and providing legal assistance to enhance the system’s sustainability and fairness.